Analisa ekonomis peralatan pulverizer untuk optimalisasi keandalan PLTU dengan simulasi Monte Carlo dan pendekatan analisa biaya siklus hidup (Studi kasus: PLTU X) - Reza Firdian Mardiansyah; Elisa Kusrini; Faisal RM (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
To improve and maintain the reliability of PLTU X (FTP-1) power supply using coal fuel it is necessary to improve the reliability of the equipment especially on the crucial equipment which one of the pulverizer equipment for it is necessary to process the procurement of equipment components (stock warehouse) to maintain if possible a malfunction or malfunction occurs. The author intends to make three alternative procurement process that is through OEM procurement process, Non OEM / reverse engineering and recondition.This journal will analyze a financial feasibility study to ascertain whether the procurement has economic value and the asset will be used effectively and efficiently over the life of the benefit using the LCCA cost analysis approach. In this paper, historical data on pulverizer damage is obtained from the HDKP Rapsodi Settlement application to be verified and processed using minitab 17 applications to obtain the weibull shape factor (β) and scale factor / characteristic life () and the data as monte carlo simulation input. So we get mean time to failure (MTTF) / age of pulverizer component. To analyze the threealternatives and determine which alternatives are most profitable for 10 years with a life cycle cost analysis approach.Based on the analysis of quantitative calculation data, the life of pulverizer mills (MTTF) procurement process OEM for 10,108 hours / 1.2 years, non-OEM / reverse engineering for 16,899 hours / 2 years and recondition for 5,323 hours / 0.7 years and the results of approach life cycle cost analysis was obtained cost savings of 35.22 billion per unit pulverizer mills for 10 years with reverse engineering procurement process compared to OEM.